The impact of sleep interventions combined with enhanced nutritional support on sleep quality, nutritional status, pain management, psychological well-being, and quality of life in postoperative colon cancer patients - Gang Wang; Shengjie Pan (Journal of Cancer Research and Clinical Oncology)
Abstract Objective To investigate the synergistic effects of combined sleep interventions and enhanced nutritional support on postoperative recovery in colon cancer patients, with a focus on sleep quality, nutritional status, pain management, psychological well-being, and quality of life. Methods This randomized controlled trial included 290 postoperative colon cancer patients admitted to the First Affiliated Hospital of Soochow University between May 2021 and May 2023. Participants were randomized into two groups: the intervention group, which received standard care supplemented with sleep and nutritional interventions, and the control group, which received standard care alone. Outcomes were assessed pre- and post-intervention, including the Pittsburgh Sleep Quality Index (PSQI), nutritional markers (serum albumin, prealbumin, body weight, etc.), Visual Analog Scale (VAS) for pain, Self-Rating Anxiety and Depression Scales (SAS, SDS), and EORTC QLQ-C30 quality of life scores. Results The intervention group demonstrated significantly greater improvements across all assessed domains compared to the control group ( P < 0.005 after Bonferroni correction). Sleep quality (PSQI: 7.81 vs. 10.43, d = 0.81) and nutritional markers (e.g., prealbumin: 230.19 mg/L vs. 188.01 mg/L, d = 1.21 ) improved markedly. Similarly, reductions in pain (VAS: 2.65 vs. 5.19,d = 1.09 ), anxiety (SAS: 42.03 vs. 49.45, d = 0.88), and depression (SDS: 38.17 vs. 49.77,d = 1.02 ) were observed. Quality of life scores significantly increased in the intervention group compared to the control group (EORTC QLQ-C30: 99.29 vs. 88.41, d = 0.92). Conclusion The combined intervention of sleep enhancement and nutritional support significantly accelerated postoperative recovery in colon cancer patients, demonstrating synergistic effects that improved physical, psychological, and quality-of-life outcomes. These findings underscore the value of integrating multifaceted interventions into standard postoperative care to optimize recovery trajectories and overall well-being.